Comorbidities and laboratory changes of sudden sensorineural hearing loss: a review - Xie, Wen; Karpeta, Niki; Tong, Busheng; Liu, Yuehui; Zhang, Zhilin; Duan, Maoli (Frontiers in Neurology, 2023)
Sudden sensorineural hearing loss (SSNHL) is defined as an abrupt hearing loss of more than 30 dB in three contiguous frequencies within 72 h. It is an emergency disease requiring immediate diagnosis and treatment. The incidence of SSNHL in Western countries' population is estimated between 5 and 20 per 1,00,000 inhabitants. The etiology of SSNHL remains unknown. Due to the uncertainty of the cause of SSNHL, at present, no specific treatment targets the cause of SSNHL, resulting in poor efficacy. Previous studies have reported that some comorbidities are risk factors for SSNHL, and some laboratory results may provide some clues for the etiology of SSNHL. Atherosclerosis, microthrombosis, inflammation, and the immune system may be the main etiological factors for SSNHL. This study confirms that SSNHL is a multifactorial disease. Some comorbidities, such as virus infections, are suggested to be the causes of SSNHL. In summary, by analyzing the etiology of SSNHL, more targeting treatments should be used to achieve a better effect.